2022
DOI: 10.1002/tesq.3120
|View full text |Cite
|
Sign up to set email alerts
|

How Does Having a Good Ear Promote Instructed Second Language Pronunciation Development? Roles of Domain‐General Auditory Processing in Choral Repetition Training

Abstract: Growing evidence suggests that auditory processing ability may a crucial determinant of language learning, including adult second language (L2) speech learning. The current study tested 47 Chinese English-as-a-Foreign-Language students to examine the extent to which two types of auditory processing, i.e., perceptual acuity and audiomotor integration, related to improvements in the comprehensibility and nativelikeness of L2 speech following two weeks of choral repetition training (i.e., shadowing). All particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 74 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…In terms of auditory processing (the main focus of this article), previous studies have demonstrated that those with more precise acuity can benefit from input-based phonetic training (Lengeris & Hazan, 2010). Future studies can further explore what type of training can most benefit L2 learners with greater attentional control (e.g., training with and without noise; cf., Mora et al, 2022) and audio-motor integration (e.g., output-based training; cf., Shao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of auditory processing (the main focus of this article), previous studies have demonstrated that those with more precise acuity can benefit from input-based phonetic training (Lengeris & Hazan, 2010). Future studies can further explore what type of training can most benefit L2 learners with greater attentional control (e.g., training with and without noise; cf., Mora et al, 2022) and audio-motor integration (e.g., output-based training; cf., Shao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…First of all, to be able to examine aptitude-treatment interactions (e.g., whether a given treatment is particularly useful for someone with certain characteristics; see DeKeyser, 2021), researchers must have an outcome measure that can index an individual's ability. On the contrary, when RT differences are used as a group-level outcome, the researcher's hands are tied, because the moderation analysis can no longer reveal differential treatment effects that are based on the characteristics of the learner, such as perceptual abilities (e.g., sound discrimination skills; Shao et al, 2023) and cognitive abilities (e.g., working memory capacity; Suzuki & DeKeyser, 2017). Therefore, when the outcome does not tap into one's ability at the individual level, the analysis itself is not meaningful.…”
Section: Rt Differences As An Individual Measurementioning
confidence: 99%
“…Such learning environments do not provide an abundant amount of contextually rich, communicatively authentic input (Shintani et al, 2013). Owing to the asymmetry here (output > input), learners’ audio-motor integration (but not perceptual acuity) has been found to impact the outcomes of classroom L2 speech learning (e.g., Saito et al, 2021 for Vietnamese EFL classrooms; Shao et al, 2022 for Chinese EFL classrooms).…”
Section: Future Directionsmentioning
confidence: 99%
“…There is also a possibility that learners’ degree of auditory precision in general (relatively strong or relatively poor) could help determine the extent to which they might benefit from phonetic training (using speech stimuli) and auditory training (using non-speech stimuli). Provision of phonetic training alone could be sufficient for L2 learners with strong auditory processing skills as they are more capable of encoding the acoustic dimensions of new sounds and are likely to show larger gains when they receive various types of intensive L2 speech training (see Lengeris & Hazan, 2010 for high variability phonetic training; Shao et al, 2022 for shadowing training; Sun et al, 2021 for five months of study abroad).…”
Section: Future Directionsmentioning
confidence: 99%